DETERMINATION OF INTEREST IN USING E-WALLET IN THE ACCOUNTING INFORMATION SYSTEM IN LHOKSEUMAWE CITY - Shara Amelia Putri; Almunadiya; Venna Maulida Mustika; Ismed Wijaya; Sakina Putri (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The development of digital payment systems through the use of electronic wallets (e-wallets) is part of the transformation of technology-based accounting information systems. The Technology Acceptance Model (TAM) explains that perceived ease of use and perceived usefulness are the main factors influencing technology acceptance (Davis, 1989). This study aims to analyze the influence of perceived ease of use and perceived usefulness on the interest in using e-wallets as an accounting information system among the people of Lhokseumawe City. This study used a quantitative approach with a survey method of 100 respondents. Data were analyzed using multiple linear regression with the help of SPSS. The results showed that perceived ease of use and perceived usefulness have a positive and significant effect on interest in using e-wallets, both partially and simultaneously. This finding supports the TAM model and indicates that increased ease of use and perceived usefulness will encourage interest in using e-wallets as part of a digital accounting information system.